Macaques at the margins: the biogeography and extinction of Macaca sylvanus in Europe - Elton, Sarah; O'Regan, Hannah J. (Elsevier, 2014)
The genus Macaca (Primates: Cercopithecidae) originated in Africa, dispersed into Europe in the Late Miocene and resided there until the Late Pleistocene. In this contribution, we provide an overview of the evolutionary history of Macaca in Europe, putting it into context with the wider late Miocene, Pliocene and Pleistocene European monkey fossil record (also comprising Mesopithecus, Paradolichopithecus, Dolichopithecus and Theropithecus). The Pliocene and Pleistocene European Macaca fossil material is largely regarded as Macaca sylvanus, the same species as the extant Barbary macaque in North Africa. The M. sylvanus specimens found at West Runton in Norfolk (53°N) during the Middle Pleistocene are among the most northerly euprimates ever discovered. Our simple time-budget model indicates that short winter day lengths would have imposed a significant constraint on activity at such relatively high latitudes, so macaque populations in Britain may have been at the limit of their ecological tolerance. Two basic models using climatic and topographic data for the Last Interglacial and the Last Glacial Maximum alongside Middle and Late Pleistocene fossil distributions indicate that much of Europe may have been suitable habitat for macaques. The models also indicate that areas of southern Europe in the present day have a climate that could support macaque populations. However, M. sylvanus became locally extinct in the Late Pleistocene, possibly at a similar time as the straight-tusked elephant, Palaeoloxodon antiquus, and narrow-nosed rhinoceros, Stephanorhinus hemitoechus. Its extinction may be related to vegetation change or increased predation from Homo, although other factors (such as stochastic factors occurring as a result of small population sizes) cannot be ruled out. Notwithstanding the cause of extinction, the European macaque may thus be a previously overlooked member of the Late Pleistocene faunal turnover.